2022
DOI: 10.3389/fped.2022.912784
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of pediatric patients with symptomatic SARS-CoV-2 infection during the first months of the COVID-19 pandemic in a single center in Mexico City

Abstract: BackgroundThe clinical spectrum of COVID-19 is broad, from asymptomatic to severe cases and death. The objective of this study is to analyze the clinical course of patients attended during the first months of the SARS-CoV-2 pandemic in a third-level pediatric hospital.MethodsDesign: prospective cohort study. Patients with viral respiratory disease or suspected cases of COVID-19 were evaluated at the Pediatric Hospital, National Medical Center XXI Century, Mexico City, from 21 March 2020 to 13 January 2021. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 28 publications
0
15
1
Order By: Relevance
“…The mortality rate of our patients was higher than that reported in high‐income countries, including multicentre studies (3–9%) 29–31 . It was also higher than that reported in India (10%), Turkey (6.9%) and Mexico City (7.1%) 15,16,23 . In addition, there were no reported deaths among hospitalised children with MIS‐C in Cape Town, South Africa, according to Butters et al 24 …”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…The mortality rate of our patients was higher than that reported in high‐income countries, including multicentre studies (3–9%) 29–31 . It was also higher than that reported in India (10%), Turkey (6.9%) and Mexico City (7.1%) 15,16,23 . In addition, there were no reported deaths among hospitalised children with MIS‐C in Cape Town, South Africa, according to Butters et al 24 …”
Section: Discussioncontrasting
confidence: 53%
“…[29][30][31] It was also higher than that reported in India (10%), Turkey (6.9%) and Mexico City (7.1%). 15,16,23 In addition, there were no reported deaths among hospitalised children with MIS-C in Cape Town, South Africa, according to Butters et al 24 The increased mortality rate observed in our study could be attributed to the following factors: first, the majority of these patients were referred from other health-care facilities and had a serious spectrum of illnesses at the time of enrolment (64.4% had respiratory manifestations, 48.9% had coma, 44.4% had shock, 33.3% had seizures, 22.2% had cerebrovascular stroke, 26.7% had evidence of myocarditis, 6.7% had recent dilated cardiomyopathy, 2.2% had coronary artery aneurysm and 2.2% had pericardial effusion); second, asymptomatic cases and patients with mild clinical manifestations who could be treated in primary care were not included in this study; third, the mortality rate in our study could have been reduced if we had used ECMO, which is not currently available at our hospital; and fourth, patients with MIS-C overlapping severe acute COVID-19 had evidence of respiratory involvement, as our study results showed, and the majority of these children had a positive PCR for SARS-CoV-2 with negative serology, and their mortality rate was higher. We hypothesise that early identification of patients and the availability of resources are critical for timely health-care delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children and adolescents are less likely to develop severe COVID-19 manifestations. Previous studies mentioned that patients with underlying medical conditions are more susceptible to severe illness with higher hospitalization and mortality rates ( 13 , 23 , 26 , 32 ). In a cross-sectional study on 43,465 pediatric patients with COVID-19 by Kompaniyets et al, the significant risk factors for hospitalization were type 1 diabetes and obesity.…”
Section: Discussionmentioning
confidence: 99%